Congenital Lung Malformations: Unresolved Issues and Unanswered Questions - Annunziata, Federica; Bush, Andrew; Borgia, Francesco; Raimondi, Francesco; Montella, Silvia; Poeta, Marco; Borrelli, Melissa; Santamaria, Francesca (Frontiers in Pediatrics, 2019)
Advances in prenatal and postnatal diagnosis, perioperative management, and postoperative care have dramatically increased the number of scientific reports on congenital thoracic malformations (CTM). Nearly all CTM are detected prior to birth, generally by antenatal ultrasound. After delivery, most infants do well and remain asymptomatic for a long time. However, complications may occur beyond infancy, including in adolescence and adulthood. Prenatal diagnosis is sometimes missed and detection may occur later, either by chance or because of unexplained recurrent or persistent respiratory symptoms or signs, with difficult implications for family counseling and substantial delay in surgical planning. Although landmark studies have been published, postnatal management of asymptomatic children is still controversial and needs a resolution. Our aim is to provide a focused overview on a number of unresolved issues arising from the lack of an evidence-based consensus on the management of patients with CTM. We summarized findings from current literature, with a particular emphasis on the vigorous controversies on the type and timing of diagnostic procedures, treatments and the still obscure relationship between CTM and malignancies, a matter of great concern for both families and physicians. We also present an algorithm for the assessment and follow-up of CTM detected either in the antenatal or postnatal period. A standardized approach across Europe, based on a multidisciplinary team, is urgently needed for achieving an evidence-based management protocol for CTM.